2020
DOI: 10.1115/1.4047322
|View full text |Cite
|
Sign up to set email alerts
|

Improved Method for the Estimation of Minimum Miscibility Pressure for Pure and Impure CO2–Crude Oil Systems Using Gaussian Process Machine Learning Approach

Abstract: The minimum miscibility pressure (MMP) is one of the critical parameters needed in the successful design of a miscible gas injection for enhanced oil recovery purposes. In this study, we explore the capability of using the Gaussian process machine learning (GPML) approach, for accurate prediction of this vital property in both pure and impure CO2-injection streams. We first performed a sensitivity analysis of different kernels and then a comparative analysis with other techniques. The new GPML model, when comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Li et al [28] evaluated the reliability of four machine learning-based prediction models including neural network analysis (NNA), genetic function approximation (GFA), multiple linear regression (MLR), and partial least squares (PLS) using 136 sets of data. Other machine learning models have also been developed for MMP prediction, such as those developed by the authors of [18,[29][30][31][32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al [28] evaluated the reliability of four machine learning-based prediction models including neural network analysis (NNA), genetic function approximation (GFA), multiple linear regression (MLR), and partial least squares (PLS) using 136 sets of data. Other machine learning models have also been developed for MMP prediction, such as those developed by the authors of [18,[29][30][31][32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…With regard to classical forecasting methods, ARIMA and SARIMA models have been used successfully in plentiful applications such as oil price prediction [6][7][8][9]. The two models for our proposed experiments are considered supervised learning; hence, machine learning algorithms may be applied to create a model based on training data to make predictions or judgments without being explicitly programmed [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [ 29 ], we compared four estimation methods and found that the machine learning intelligent algorithm had a higher precision to the MMP than pure linear model. In addition, some reports that combined multiple approaches showed better results [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%